Encephalitis and myositis caused by Trachipleistophora hominis diagnosed by metagenomic next-generation sequencing—a case report - Zheng, Haipeng; Tan, Ying; Chen, Xudan; Chen, Jinfeng; Li, Linghua; Wang, Jian (Frontiers in Cellular and Infection Microbiology, 2023)
Background Myositis is the main manifestation of Trachipleistophora hominis (T. hominis) infection and other microsporidians infection in immunocompromised patients. Clinical differential diagnosis of different microsporidians can be challenging, as the standard technique to distinguish various microsporidia species, transmission electron microscopy (TEM), is time-consuming and relies on equipment and experienced staffs who can perform the test and interpret the results. Case presentation We report a 37-year-old Chinese man with acquired immune deficiency syndrome (AIDS) developed headache and muscle pain in the extremities. Tramadol was used to relieve his pain. Infectious lesions in his brain were detected by cerebral magnetic resonance imaging (MRI). Oval-shaped pathogens was observed by biopsy of right gastrocnemius. Finally, T. hominis was identified by metagenomic next-generation sequencing (mNGS) in the gastrocnemius tissue and cerebrospinal fluid. After a 12-week course of antifungal treatment and antiretroviral therapy, the patient recovered from the encephalitis and myositis caused by T. hominis. Conclusion This report described the diagnosis and treatment of the first case of encephalitis caused by T. hominis. And mNGS is recommended for the rapid diagnosis of uncommon pathogens.